Design parameters of boric acid production process from colemanite ore in the presence of propionic acid - Kuskay, B.; Bulutcu, A.N. (Elsevier BV, 2011)
Abstract In this study, three different boric acid production process alternatives which can be performed in the presence of propionic acid and/or calcium propionate were evaluated. The process in which calcium propionate is the recycling component was selected as the best alternative and modeled. Some of the design parameters were determined for the selected process. These parameters are solubility change of boric acid in the presence of calcium propionate at 25 °C, 35 °C and 75 °C, precipitation risk of calcium borate components in concentrated boric acid solutions containing calcium propionate, and the effect of calcium propionate on the solution pH with respect to free sulfuric acid concentration. According to the determined parameters, principal reactions occurred in the process, and other process parameters obtained by industrial practice, mass balances were conducted and all flow rates were calculated. In the process, calcium propionate concentration in production liquor must be kept lower than 3% and the reaction must be carried out without any free sulfuric acid in order to perform the process according to the model.